Pengembangan Mesin Pengupas Bawang Merah Berkapasitas Tinggi dan Sistem Pengelolaan Sampah yang Efisien untuk Mendukung Industri Kuliner di Kota Makassar - Muttaqin, Ahmad Nurul; Mihdar, Uswatul Hasanah; Ilmunandar, Alief Maulana; Arfandy, Arfandy; Halim, Abdul; Ariputra, A. (Manutech : Jurnal Teknologi Manufaktur, 2025)
This study focuses on the design and performance evaluation of a shallot peeling machine aimed at enhancing processing efficiency for culinary applications. The machine is equipped with a ¼ hp electric motor operating at 1400 rpm, along with a specially designed peeling disc that utilizes rubber friction around the drum to effectively peel the shallots. The machine’s large-capacity container is designed to prevent the test materials from being ejected during operation, ensuring stability throughout the peeling process. Testing was conducted in two stages: the first stage used 1 kg of shallots, and the second stage used 2 kg, both at a motor speed of 1400 rpm. In the first test stage, the machine achieved an average peeling efficiency of 82% after one minute (equivalent to 820 grams of peeled shallots from 1 kg), which increased to 94.2% (942 grams) after two minutes and reached 98.5% (985 grams) after three minutes. In the second test stage with 2 kg of shallots, the machine recorded an average peeling efficiency of 96.4% (1929 grams). The machine demonstrates a production capacity of 30 kg per hour, far exceeding the previous model's capacity of only 14 kg per hour. These findings confirm that the newly designed shallot peeling machine meets performance expectations and offers a substantial improvement in peeling efficiency and productivity.